Cubizpay: Information System in Credit Unions - YUSUF, Rolland M.; PARANOAN, Selmita (International Journal of Environmental, Sustainability, and Social Science, 2026)
Credit Unions, as a place for human empowerment, have inefficiencies in their operational activities due to the lack of information systems needed by Credit Union members in making transactions, resulting in a decrease in member trust in Credit Unions. In 2021, Credit Union Indonesia presents CubizPay as a media for member transactions. This research aims to determine the benefits of CubizPay in increasing member trust in Credit Union services. This research applies an interpretative approach with interpretative phenomenological analysis, to find out the meaning of user experience in accepting and using CubizPay through interviews and documentation with (5) Credit Union members who are active CubizPay users. This research found that the benefits of CubizPay can increase member trust through transaction transformation in member activities, which is equipped with a reliable security system to protect member transaction, as well as internal controls that help minimize risks in the Credit Union environment. CubizPay as an information system in Credit Unions is known to be able to increase member trust and help the Credit Union’s operational activities. This research analysis to introduces CubizPay as an information system for Credit Unions in Indonesia.